Re-Imagining Society and Childhood: An Analysis of Cultural Politics of Childhood in Turkey - TORAN, MEHMET; Toprak, Ziya (Sage Publications Inc., 2022)
Neoliberalism along with other sites of cultural, social and political life has created deep impacts on childhood. With the rise of neoliberalisation of policies, childhood has come to be defined in terms of economic utility and wellbeing of society. In this paper, we examine the process of neoliberalisation through the changing role and meaning of childhood. We inquire the role of childhood in re-imagining of the Turkish society based on the data from the document of the strategic vision of the Turkish government. We seek to track the evolving notion of childhood and roles ascribed to it. By applying a critical discourse lens to the document of 8th Five Year Development Plan and Strategic Vision of 2023, we explain how the cultural politics of childhood work as tools of creating present and future workers. We examine the shifting place of childhood and instrumentalisation of childhood in neoliberal imagination of policy.
Keywords: Childhood; Cultural Politicsdis; Policy